ANTIMYCOBACTERIAL, ANTIMICROBIAL AND ANTIFUNGAL ACTIVITIES OF GERANIUM OIL-LOADED NANO CAPSULES - Giongo, Janice Luehring; Vaucher, Rodrigo De Almeida; Borin, Diego; CORREA, MARCOS SALDANHA; Dos Santos, Victor Barboza; Vianna Santos, Roberto Christ; Boligon, Aline Augusti; Athayde, Margareth Linde; Bonez, Pauline Cordenonzi; Rossi, Grazielle Guidolin; et al. (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: The aim of this study was to perform the first ever investigation of the effect of activities in theÂ nano capsulesÂ containingÂ Geranium oil (NC1) against different species of pathogens such as Mycobacterium genus (both fast growing and slow growing), bacterial, and yeasts. Methods: The GOÂ was analyzed by GC and GC/MS. Nano capsule suspensions (NC) were prepared by interfacial deposition of a preformed polymer method and the MICs were determined for the antimycobacterial, antimicrobial,Â and antifungal activities. Results: GO-loaded nano capsules (NC1) presented nano metric mean diameters (188 nm), polydispersity indices below 0.149, pH (5.5), and zeta potentials (about-10.8 mV). The MICs were determined for the antimycobacterial, antimicrobial,Â and antifungal activities. The NC1 was effective to Mycobacterium smegmatis (149.7 Âµg ml-1), M. abscessos (35.9 Âµg ml-1), M. massiliense (35.9 Âµg ml-1), M. avium (71.8 Âµg ml-1), Enterococcus faecalis, Streptococcus sp. (149.7 Âµg ml-1) and Listeria monocytogenes (35.9 Âµg ml-1). The NC1 was able to significantly reduce the number of cells of C. albicans (by approximately 5 log), 4 log the number of cells of C. dublinensis, C. glabrata, and C. krusei, and 2 log the number of cells of C. parapsilosis compared to the control group. Conclusion: Our study showed that the geranium oil-loaded nano capsules have antimycobacterial activities similar to free oil. The GO was effective in inhibiting the formation of germ tubes of Candida albicans, yet the nano capsule containing GO failed to inhibit the formation of this important virulence factor. Â